An Update on Stem Cell Scaffolds using Tissue Engineering for Clinical Applications - G. Subramanyam; Mahaboob V. Shaik (Technological Innovation in Engineering Research Vol. 8, 2022)
Successful stem cell-based tissue engineering requires a combination of progenitors with lineage potential, growth factors, cell-friendly scaffold biomaterials, and suitable bio-factors to enhance specific differentiation, and prominent function. In this review, we focus on the biocompatibility and cell-friendly scaffold materials, inorganic/organic synthetic compounds, natural and synthetic polymers, decellularized extracellular materials, and scaffolds. It is possible that combinations of these bioactive materials, progenitors, growth factors, biomimetic scaffolds with 3D bioprinting technology, allow a new era of bioengineering based modality to patient specific applications or therapeutics.